Implementasi Akad Istishna (PSAK Syariah 104) dalam Transaksi Jual Beli Online - Pekerti, Retno Dyah; Faridah, Eva; Hikmatyar, Missi; Rudiana, Irfan Faris (IAIN Kudus, 2021)
Online buying and selling transactions are growing rapidly, from an Islamic perspective, they fall into the jurisprudence muamalah category of business or commerce. In Islam, there are rules governing buying and selling transactions that must be carried out by the seller and the buyer. This research is to explore the pillars and requirements for online buying and selling transactions and the implementation of the Istishna contract which refers to the Islamic PSAK 104 in online transactions. A qualitative method with case study research conducted in Tasikmalaya was chosen as the method in this research. The informants in the research are business people, consumers, academics, and ustadz. The results show that business people generally know about the pillars and requirements for online buying and selling transactions from an Islamic perspective. The Istishna contract has been carried out by business people with the term pre-order, business people do not know and apply the Sharia PSAK 104. The research can be a reference for business people, academics, and input for regulators and the public.